GRAVITY FIELD IN EXTERNAL PARTS OF THE SOLAR SYSTEM - Bazey, N. V.; Bazey, A. A. (Одеські астрономічні публікації, 2012)
Taking into account the gravitational perturbations from the center of the galaxy and using the catalogue closest to the Sun, stars modeled surfaces of equal gravitational potential energy fields in the outskirts of the solar system. Constructed three-dimensional model of equipotential surfaces in the vicinity of the solar system. It is shown that for certain values a constant of the energy the Sun is within the common equipotential surface Toliman, Sirius and Procyon.